EVALUASI PEMILIHAN SUPPLIER BESI PADA PT.XYZ MENGGUNAKAN METODE ANALYTICAL NETWORK PROCESS (ANP) DAN TECHNIQUE FOR OTHERS PREFERENCE BY SIMILARITY TO IDEAL SOLUTION (TOPSIS) - Rafid Amarullah (2023)
Procurement is an activity that aims to obtain goods that are used to obtain goods used for the benefit of the company obtained from suppliers to facilitate the production that is being carried out by the company. PT. XYZ is one of the property development companies responsible for the land acquisition process, land price negotiation, land clearing, making master plans, to the stage of determining the house model. In this study, the Analytical Network Process (ANP) method is used as a weighting of criteria and subcriteria for supplier evaluation and testing of the level of consistency in the importance of each criterion in pair comparison, while the Technique For Others Preferences by Similarity to Ideal Solution (TOPSIS) method is used to rank based on suppliers who have collaborated in procuring products at the company. Based on the results of the study, price criteria were obtained with the highest cluster normalization weight values, namely H1, H4, H5, and H2 subcriteria. Furthermore, the quality criteria with the highest to lowest normalization weight values are subcriteria K3, K4, then K1. Furthermore, the delivery criteria with the highest to lowest normalization weight values are subcriteria P3, P2, then P1. Furthermore, the response criteria with the highest to lowest normalization weight values are subcriteria R2 then R1. Furthermore, the service criteria with the highest to lowest normalization weight values are S3 subcriteria then S2. Furthermore, the legal criteria with the highest to lowest normalization weight values are subcriteria L1 and then L2. In the ranking of the best suppliers, supplier D was obtained with a value of 0.747, became the best iron procurement supplier, followed by supplier A with a value of 0.401, supplier B with a value of 0.394, and supplier C with a value of 0.331.